Friendships for wellbeing?: parents' and practitioners' positioning of young children's friendships in the evaluation of wellbeing factors. Issue 4 (2nd October 2019) - Brogaard-Clausen, Sigrid; Robson, Sue
ABSTRACT: Friendship matters for young children's development, learning and experience of wellbeing. This paper emphasises the significance of young children's friendships for their wellbeing, especially in the context of early years settings. Findings are presented from two online questionnaires developed for the project, in which 155 parents/carers and 285 practitioners in England expressed their perceptions of what matters for young children's wellbeing. Data shows some ambivalence in the views of both parents/carers and practitioners about the importance of friendship in this context. Both groups gave low prioritisation to 'the company of friends' for children's wellbeing. As friendships are of central importance to young children themselves, this could suggests that adults and children may have different priorities, which raises questions about the extent to which young children's friendships are seen as important by adults. The paper concludes by proposing the need for practitioners in particular, but also parents, to consider their roles and priorities for children's lives within schools and nurseries, including how they might sensitively support and facilitate children's friendships in play, activities, transition and everyday life.